Faktor-Faktor Yang Memengaruhi Kemiskinan Secara Langsung Dan Tidak Langsung Di Nusa Tenggara Timur - Yezua Abel; Rani Nooraeni; Eni Lestariningsih (Badan Pusat Statistik Provinsi NTT, 2023)
Poverty is still a central issue for East Nusa Tenggara Province because alleviation efforts have not experienced a significant reduction. Lots of studies on poverty had been carried out during the pre-pandemic period, but after the pandemic, research on poverty has not been carried out much. This research analyzes the direct and indirect effects of economic growth, the human development index on unemployment and the poverty rate in NTT to obtain information that can support development policies. Data sourced from BPS and data analysis using path analysis. The results of the study show that the HDI has a significant effect on unemployment, while economic growth has no significant effect. Together economic growth and HDI can explain significant variations in unemployment. Unemployment has a fairly strong negative effect on poverty while economic growth and HDI do not have a significant effect. Together economic growth, HDI, and unemployment can explain significant variations in poverty. Economic growth and HDI do not have an indirect effect through unemployment on poverty.